2020
DOI: 10.1021/acs.energyfuels.9b04430
|View full text |Cite
|
Sign up to set email alerts
|

Production of New Surfactant-free Microemulsion Biofuels: Phase Behavior and Nanostructure Identification

Abstract: New surfactant-free microemulsion biofuels are synthesized and characterized in this work. Moringa and safflower plants have been used for providing the required oils because of their excellent resistance in dry and harsh environmental conditions. Methyl tert-butyl ether (MTBE), 1-heptanol, 1-octanol, oleic acid, 1,4-dioxane, and dibutyl ether have been used as biofuel additives. The obtained phase behavior results show that the microemulsion region of ternary phase diagrams in these systems decreases as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…With the further increase in W OA (more than 31.4 wt %), the water-in-oil (W/O) microemulsion is formed with n -octane as the continuous phase. In this stage, the κ value only relies on the movability of water droplets, but the reduced proportion of water droplets in the system with the increasing W OA results in a linear decrease in the κ value. , Therefore, the O/W, B.C, and W/O microregions in the single-phase region are distinguished (Figure ) through the measurements of the changing κ values with different R P/W and W OA values.…”
Section: Resultsmentioning
confidence: 99%
“…With the further increase in W OA (more than 31.4 wt %), the water-in-oil (W/O) microemulsion is formed with n -octane as the continuous phase. In this stage, the κ value only relies on the movability of water droplets, but the reduced proportion of water droplets in the system with the increasing W OA results in a linear decrease in the κ value. , Therefore, the O/W, B.C, and W/O microregions in the single-phase region are distinguished (Figure ) through the measurements of the changing κ values with different R P/W and W OA values.…”
Section: Resultsmentioning
confidence: 99%
“…The surfactant systems form micelles, which form aggregates and extract the inhibitory compounds when the temperature is above the surfactant's cloud point. It was also observed that micro micelles or reverse micelles enhance the enzymatic hydrolysis at the interface or core of micelles, by stimulating the in vivo environment of microbes which is favourable for the activity of the enzymes 66,283 …”
Section: Organic Nanoparticles That Are Used In Biofuel Productionmentioning
confidence: 99%
“…It was also observed that micro micelles or reverse micelles enhance the enzymatic hydrolysis at the interface or core of micelles, by stimulating the in vivo environment of microbes which is favourable for the activity of the enzymes. 66,283…”
Section: Micellesmentioning
confidence: 99%
“…In order to blend the oxygenated additive with diesel, it was necessary to form a microemulsion using a co-surfactant [17][18][19][20]. In this sense, microemulsions with heptanol are those that present characteristics closer to diesel [21], so it was selected as a co-surfactant.…”
Section: Biofuels Formulationmentioning
confidence: 99%
“…They were three-phase mixtures. The continuous phase was biodiesel/diesel, the dispersed phase was the oxygenated additive and heptanol acted as co-surfactant [21][22][23].…”
Section: Biofuels Formulationmentioning
confidence: 99%